2022
DOI: 10.1186/s40164-022-00281-2
|View full text |Cite
|
Sign up to set email alerts
|

The importance of N6-methyladenosine modification in tumor immunity and immunotherapy

Abstract: As the most common and abundant RNA modification in eukaryotic cells, N6-methyladenosine (m6A) modification plays an important role in different stages of tumor. m6A can participate in the regulation of tumor immune escape, so as to enhance the monitoring of tumor by the immune system and reduce tumorgenesis. m6A can also affect the tumor progression by regulating the immune cell responses to tumor in tumor microenvironment. In addition, immunotherapy has become the most popular method for the treatment of can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 133 publications
0
7
0
Order By: Relevance
“…Tumor-infiltrating immune cells are highly heterogeneous and have been shown to play important roles in immune evasion and the response to immunotherapy treatment ( 31 ). In the present study, the total macrophages from cancer and paracancer tissue were extracted, and they exhibited 12 distinct subclusters ( Figure 3A ), The tSNE plot shows the subcluster distribution among the sample pathology ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Tumor-infiltrating immune cells are highly heterogeneous and have been shown to play important roles in immune evasion and the response to immunotherapy treatment ( 31 ). In the present study, the total macrophages from cancer and paracancer tissue were extracted, and they exhibited 12 distinct subclusters ( Figure 3A ), The tSNE plot shows the subcluster distribution among the sample pathology ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…For decades, an increasing number of studies have shown that m6A mRNA modification affects the biology of normal and tumor cells [ 31 34 ]. STM2457, a new bioavailable inhibitor of METTL3, was developed in 2021 as a new drug to treat myeloid leukemia [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, immunotherapy has become the most popular cancer treatment method, among which targeting immune checkpoints is also closely related to m 6 A [ 96 ]. In the above, we discussed various mechanisms of immune evasion and immune regulation by m 6 A modification in cancer.…”
Section: Immune Infiltration Of M 6 a In Esophagea...mentioning
confidence: 99%
“…Inhibition of FTO can reduce tumor resistance to PD-1 treatment [ 88 ]. In addition to immunotherapy targeting PD-1, m6A modification is also involved in the regulation of cytotoxic T-lymphocyte antigen 4(CTLA-4) targeted therapy [ 96 ]. In addition, m 6 A modification has also been implicated in the regulation of TIM3 (T-cell immunoglobulin-3), TIGIT (T Cell Immunoreceptor With Ig And ITIM Domains) and LAG3(Lymphocyte Activation Gene3) [ 96 ].…”
Section: Immune Infiltration Of M 6 a In Esophagea...mentioning
confidence: 99%
See 1 more Smart Citation